(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Internet access in rural areas of Cajamarca, specifically in the high Andean areas, faces significant restrictions due to poor telecommunications infrastructure, which produces digital disparities that harm education, the economy, and social inclusion. The purpose of this research was to create and implement a Backhaul network that improves connectivity in the high Andean districts, analyzing its technical feasibility and its possible effect on the quality of service. An applied methodological approach was used, with a quantitative approach and an experimental design, which included the study of traffic, network structure and the choice of appropriate equipment for areas of difficult geographical access. The findings indicated that the network presented increases the available bandwidth, decreases latency and ensures greater stability in data transmission, which enables more efficient access to the internet in remote communities. In summary, the implementation of a Backhaul network is shown to be an appropriate option to reduce the digital divide in rural areas, promoting technological inclusion and social progress in the high Andean regions.